2004
DOI: 10.1128/jvi.78.22.12438-12445.2004
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Human Immunodeficiency Virus Type 1 Subtype A Virus Circulating in West Africa: Sub-Subtype A3

Abstract: Phylogenetic analyses demonstrate significant diversity in worldwide circulating strains of human immunodeficiency virus type 1 (HIV-1). Detailed studies have revealed a complex pattern of intersubtype recombinations, as well as evidence of sub-subtypes circulating in various populations. In this study, we characterized an HIV-1 strain that had previously been identified as a distinct subcluster within the subtype A radiation based on partial sequence data. These viruses were of particular interest given that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
47
0
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 35 publications
0
47
0
2
Order By: Relevance
“…The distribution of HIV-1 genetic diversity with respect to epidemiological factors such as risk group and geographic location is highly dynamic; novel genetic diversity is continually being generated through mutation and recombination, and travel and migration promote the transfer of diverse viral strains between populations, often across large distances (19,26,37). The speed at which genetic diversity is generated by HIV-1 presents a challenge to standard phylogenetic classification systems, as reflected in the growing number of unclassifiable and complex recombinant sequences being reported (13, 34-36, 38, 44), the proliferation of "sub-subtype" nomenclature (11,23,39,45), and accumulating evidence that at least some of the established groupings are artifacts of sampling (1,2,10).…”
Section: Discussionmentioning
confidence: 99%
“…The distribution of HIV-1 genetic diversity with respect to epidemiological factors such as risk group and geographic location is highly dynamic; novel genetic diversity is continually being generated through mutation and recombination, and travel and migration promote the transfer of diverse viral strains between populations, often across large distances (19,26,37). The speed at which genetic diversity is generated by HIV-1 presents a challenge to standard phylogenetic classification systems, as reflected in the growing number of unclassifiable and complex recombinant sequences being reported (13, 34-36, 38, 44), the proliferation of "sub-subtype" nomenclature (11,23,39,45), and accumulating evidence that at least some of the established groupings are artifacts of sampling (1,2,10).…”
Section: Discussionmentioning
confidence: 99%
“…CRF16_A2D has also achieved a global spread and has been identified in Korea and Argentina (Gomez-Carrillo et al, 2004). Subsubtype A3 has only been recently described (Meloni et al, 2004a), and has thus far only been identified in areas of West and Central Africa (Meloni et al, 2004a;Meloni et al, 2004b). Similarly subsubtype A4 is a relatively new strain, and has only been identified within the Democratic Republic of Congo .…”
Section: The Global Distribution Of Hiv-1 Subtypes and Crfsmentioning
confidence: 99%
“…However, recent work conducted in our lab revealed that a unique group of viruses within the human immunodeficiency virus type 1 (HIV-1) subtype A radiation is also present in the FSW study population (40,42). Through phylogenetic analyses, we have shown that this subcluster of viruses can be classified as HIV-1 sub-subtype A3 (30). The goal of the current investigation was to understand the distribution and dynamics of HIV-1 A3 in the Dakar FSW cohort.…”
mentioning
confidence: 99%
“…Manual adjustments, when necessary, were made by using the MacClade version 4.05 program (Sinauer Associates, Inc., Sunderland, Mass.). For reference A3 sequences, we used AY521629 (DDI579), AY521630 (DDJ360), and AY521631 (DDJ369) (30). Phylogenetic analyses were performed, using the SEQBOOT, DNADIST, NEIGHBOR, and CONSENSE programs in the Phylip version 3.6 package (11).…”
mentioning
confidence: 99%